Rapid Initiation of Antiretroviral Therapy Suppresses T Cell Pathological Proliferation and Improves Immune Recovery in People Living with HIV - Ji J; Guo C; Li Z; Cai M; Wang R; Chen X; Zhang Y; Wu H; Zhang T; Zhang Y (Infection and Drug Resistance)
Jiahao Ji,1,* Caiping Guo,1,2,* Zhen Li,1,3,* Miaotian Cai,4 Rui Wang,1,3 Xue Chen,1 Yulin Zhang,4 Hao Wu,1 Tong Zhang,1– 3 Yang Zhang1– 3 1Center for Infectious Diseases, Beijing Youan Hospital, Capital Medical University, Beijing, 100069, People’s Republic of China; 2Beijing Institute of Sexually Transmitted Disease Prevention and Control, Beijing, 100069, People’s Republic of China; 3Beijing Key Laboratory of HIV/AIDS Research, Beijing, 100069, People’s Republic of China; 4Department of Respiratory and Critical Care Medicine, Beijing Youan Hospital, Capital Medical University, Beijing, 100069, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yang Zhang, Center for Infectious Diseases, Beijing Youan Hospital, Capital Medical University, 8 Xitoutiao, Youanmenwai, Fengtai District, Beijing, 100069, People’s Republic of China, Email zhangyangdoc@ccmu.edu.cn Tong Zhang, Center for Infectious Diseases, Beijing Youan Hospital, Capital Medical University, 8 Xitoutiao, Youanmenwai, Fengtai District, Beijing, 100069, People’s Republic of China, Email zt_doc@ccmu.edu.cnPurpose: Initiating antiretroviral therapy promptly (rapid ART) is linked to better immune recovery in people with HIV (PWH), although its specific effects on immune dysregulation remain partially understood. We have discovered a “pathological proliferation” phenomenon, marked by T cell over-proliferation and exhaustion in PWH, potentially hindering full immune recovery. The objective of this research is to examine how rapid ART affects T-cell pathological proliferation, immune recovery, and systemic inflammation in PWH.Patients and Methods: In this cross-sectional study (conducted at Beijing Youan Hospital, Capital Medical University, China, from April 1 to September 18, 2022), we recruited 39 PWH, including 23 in the rapid ART group (within 30 days) and 16 in the non-rapid ART group (after 180 days). Fasting venous blood samples were collected in the morning. Immune phenotypes of T cells were analyzed using mass cytometry and Luminex.Results: The rapid ART group demonstrated a significant decline in Ki67⁺ CD4⁺ and CD8⁺ T cells. Within this group, a higher percentage of naive T (TN) cells was observed in CD4⁺ T cells, along with a remarkable reduction in Ki67 expression. Additionally, CD8⁺ T cells in the rapid ART group exhibited an increased presence of TN cells while showing a decreased proportion of PD-1/HLA-DR/CD38 high-expressing cells. In addition, the rapid ART group exhibited significantly lower IL-18 levels. TN cells (CD31+ HLA-DR− CD38− CD57− PD-1−) and central memory T (TCM) cells (HLA-DR+ CD38− PD-1− CD57−) that were not suppressed by rapid ART showed significant correlations with baseline CD4 counts, HIV loads, and recent CD4/CD8 ratio.Conclusion: These findings suggest rapid ART may curb pathological T cell proliferation and improved immune recovery in PWH. Despite these benefits, persistent immune activation in some individuals highlights the need for targeted immune monitoring and potential adjunctive interventions to optimize long-term immune health in PWH.Keywords: rapid ART, pathological proliferation, immunological non-responders, INRs, human immunodeficiency virus, HIV